ANALYSIS OF THE RELATIONSHIP BETWEEN INTERPERSONAL INTELLIGENCE AND THE LEARNING STYLES OF YPK HEDAM MIDDLE SCHOOL STUDENTS IN JAYAPURA CITY - Rahma; Fitriani; Tb. Noer Iman Achmad Sumantri (SOSIOEDUKASI, 2025)
This study aims to examine the relationship between interpersonal intelligence and student learning styles (VARK model). The study was conducted at YPK Hedam Junior High School, Jayapura City, with 39 respondents. The research method used was a quantitative-correlational method with data collection using questionnaires on interpersonal intelligence and learning styles. In general, student preferences were more dominant in visual learning styles (71.79%) compared to auditory (17.95%) and kinesthetic (10.26%). A statistical technique called the Chi-Square test (X2 test) was used to determine the link between the learning style and interpersonal intelligence variables. A non-parametric statistical test called the Chi-Square test is used to assess if two categorical variables in a contingency table have a significant link or association. At df = 6 (12,592), the computed Chi-Square value is less than the Chi-Square table value. Furthermore, the p-value is significantly higher than 0.05. Thus, learning styles and interpersonal intelligence do not significantly correlate. This indicates that the degree of interpersonal intelligence in this data has no discernible impact on differences in student learning styles. Furthermore, to determine whether the results of this study can be generalized, future research may consider increasing the sample size